Efficiency of the seeds of tamarindus indica as a coagulant in the treatment of water intended for urban supply - González, Yoalis; Caldera, Yaxcelys; Villasmil, Danesa; González, Nauyeli; Ortiz, Yamilexi; Ortiz, Yamilexi (Impacto Científico, 2021)
Abstract inorganic chemical coagulants are the most widely used in the purification process. However, some studies link these coagulants with a detrimental effect on human health, thus generating a progression of various diseases in the nervous system. Therefore, an alternative arises to replace chemical coagulants for natural ones in water treatment. The objective of this research is to evaluate the efficiency of the seeds of Tamarindus indica in the treatment of water destined for urban supply. The coagulation-flocculation, sedimentation and filtration process was simulated by applying the doses of the coagulant extracted from the seeds of T. indica of 25, 50, 75, 100 and 125 mg/L, in diluted waters at initial turbidity of 40, 60 and 80 NTU. Physicochemical parameters turbidity, pH and color were determined. The results demonstrate the effectiveness of T. indica seeds as a coagulant, since the turbidity removal ranges between 72.30 % and 89.11 % before filtering and between 99.53 % and 99.93 % after filtering. The color removal is located before filtering between 75 % and 90 %, while the pH was not altered, varying between 5.12 and 5.94 units. The results indicate that the turbidity parameter adjusts to the limits established by the Drinking Water Quality Standards of Venezuela.